Histological Features of the Accessory Sex Gland of Indigenous Tom cat (Felis catus) Dhyaa Ab. Abood, Mohamed S. Dawood and Lamees Ezaldeen Mohammed - Dhyaa Ab. Abood; Mohamed S. Dawood; Lamees Ezaldeen Mohammed (مجلة الانبار للعلوم البيطرية, 2019)
The study was aimed to investigate the histological characteristics of the Tomcats accessory sex glands. A total of six indigenous Tom cats were used in this study. The samples of the ampulla of ductus deferens, prostate and bulbourethral glands were collected and fixed in 10% buffered formalin saline, and processed with routine paraffin technique. The tissue sections were stained by Hematoxyline & Eosin, Masson's trichrom and PAS stains. Results showed that the mucosa of ampulla has composed of tunica mucosa, muscularis, and adventitia. The tunica mucosa lined by mucous secreting cells which showed negative reaction for PAS stain and non-secreting cells which have intense reaction for PAS stain. The tunica muscularis composed of circular oriented smooth muscle fibers. The tunica adventia composed of dense irregular collagenous connective tissue. Prostate was large tubuloalveolar gland, surrounded the pelvic urethra; the gland consisted of very thick peri urethral tunica mucosa which lined with transitional epithelium. The prostatic lamina propria composed of collagen bundles, tubuloalveolar glands and manifested by many of like cavernous tissue wide veins. The prostate glandular epithelium was pseudo stratified columnar to low cuboidal which showed intense reaction for PAS stain. The muscularis of prostate composed of thick layer of skeletal muscle cells. The bulbourethral glands surrounded by a thick fibro-muscular capsule whose septa subdivided the gland into lobules. Each lobule composed of tubuloalveolar secretory units. The secretory units were lined by pseudo stratified to simple columnar epithelium supported by a thin layer of myoepithelial cells surrounds each alveolus. The cytoplasm of epithelial secretory units contained acidic secretory granules with Alcian blue (2.5pH) stains (fig.11, 12 & 13). It was concluded that tom cat's accessory glands has devoid of seminal vesicles and has well developed and functional prostate and bulbourethral glands.